Proceedings Of The Seventy-First Regular Meeting Of The Rocky Mountain Coal Mining Institute Steamboat Springs, Colorado June 29 - July 2, 1975 - Morning Session - Monday, June 30, 1975 (Rocky Mountain Coal Mining Institute, 1975)
The 71st Regular Meeting of the Rocky Mountain Coal Mining Institute convened at the Steamboat Village Inn, Steamboat Springs, Colorado, and was in session at 10:00 a.m. The session was called to order by William W. Grant, Assistant to Manager of Navajo Mine, Utah International, Inc., Fruitland, New Mexico. Mr. Grant was delegated to open the meeting due to the untimely death of Past President A. F. Geiger. Mr. Grant introduced President Roy Coulson, President and Director of the Kemmerer and Gunn-Quealy Coal Companies, Frontier, Wymoing. His biography follows: Jan. 7, 1922 Born to Jean and Joseph Coulson, Ernest, Pennsylvania 1940 Graduated - Indiana High School, Indiana, Pennsylvania